Socialist Street Names through the Lens of Postsocialism: (non)Renaming of the Streets in Ostrava and its Coverage in the Czech Press after 1989 - Kárníková, Lydie (Dějiny – teorie – kritika, 2022)
The study focuses on the issue of renaming streets as part of the process of “coming to terms with the communist past” after 1989. It examines how renaming of public spaces has become a media topic and explores it through the example of persistent socialist toponymy in Ostrava. Taking the perspective of critical toponymy and using the cultural geography concepts, the text examines the cultural memory shaped after 1989. Simultaneously, it identifies three points of view, which meet on this issue in the post-Soviet news discourse through a discourse analysis of a two-stage corpus of media texts. The paper describes the narrative of the negative experience of communism, which determines how the topic is framed in the media and which is dominant in the discourse under study. The paper therefore closes with a description of two discursive tendencies that enable and reinforce this dominance - the polarizing interpretation of national history and the use of aesthetic-cultural aversion towards the “language of communism”.